(untitled) (Research, Society and Development, 2021)
The emergence of forest fires may be of anthropic or natural origin, both of which cause significant socio-economic and environmental damage, and in the good part of these occurrences are resulting from Fire Foci (FF) occurrence. In recent years, Brazil has suffered from a significant increase in FF, resulting in large fires. In this way, the objective of the present study was to diagnose the spatiotemporal FF behavior in Brazil between 1999 à 2020, based on the BDQueimadas data of the CPTEC/INPE. The handling and processing of the data used the R version 3.4-1 environment software. After the data storage, it calculated the total, annual, and monthly records. And the composition of the most significant years, in this case, the years 2015, 2017, 2019, and 2020. The results pointed out that the most significant total and average annual accumulations ranged between 10-50 thousand FF and 0.5-1.5 thousand FF, respectively, concentrated in the central-northern region of Brazil, mainly in Maranhão, Pará, and the Tocantins. This pattern of high FC records is related to deforestation and agricultural expansion in these regions. On a monthly scale, the most significant occurrences of FF occur between August and November, with 0.2-0.45 thousand FF, due to starvation. In recent years, the El Niño-Southern Oscillation influenced the annual FF performance through the persistence of long stretches of styling, which resulted in a shortage of rainfall and large fires verified in 2020 in the Pantanal biome.